Study of environmental management systems on defence - A. Oglanis; M. Loizidou (Global Journal of Environmental Science and Management)
The effective and sustainable environmental performance of a business is a result of various factors and most important the integrated outcome of the environmental management. Likewise, the integration of environmental protection into the armed forces functions has also gain interest for the military sector internationally. Therefore, the environmental management system (EMS) is recognized as one of the most widely used tools. This study provides a review on environmental management issues related to the military activities and their assessment globally. The multitasking characteristics of the defence sector result in the need for the eco-friendly related issues to be directed in a holistic and integrated way, with the help of a certified environmental management system. North Atlantic Treaty Organization (NATO) itself and NATO countries, like USA, UK, Canada, Holland, Denmark, Czech Republic, Greece, as well as non-NATO countries like Sweden and Australia have an environmental management system structure in place to assist military environmental management and studies reveal that the armed forces could anticipate positive outcomes from environmental management system. A case-by-case approach, of the above, is examined and based on the results, appropriate recommendations are presented, which may contribute to the environmental management system considerations as the most important tool for effective management framework and most importantly to evaluate its effectiveness as a structure for the defence sector’s activities.